2013
DOI: 10.2478/s11536-012-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender effect on vascular responsiveness after bariatric surgery

Abstract: AbstractObesity, particularly abdominal obesity, is associated with increased risks of arterial hypertension, diabetes mellitus, hyperlipidemia, sleep apnea, coronary artery disease, stroke and mortality. Weight loss surgery is the most effective treatment for morbid obesity, mainly because medical and dietary treatments have been proven insufficient in the long run. Our primary end point was to study the gender effect on vascular responsiveness (endothelial function and the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 33 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…This may suggest an enhancement of the bioavailability of NO that could affect other systems, such as the inflammatory response pathway and vascular responsiveness. The improved NO availability and the possible secondary decrease in the induction of the inflammatory cascade may partially explain the improvement in endothelial function observed in these women 3 months after the operation .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This may suggest an enhancement of the bioavailability of NO that could affect other systems, such as the inflammatory response pathway and vascular responsiveness. The improved NO availability and the possible secondary decrease in the induction of the inflammatory cascade may partially explain the improvement in endothelial function observed in these women 3 months after the operation .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a gender difference in clinical, vascular, biochemical and inflammatory markers following bariatric surgery. For example, ankle–brachial index improved ( P = 0.04), systolic blood pressure decreased (by 6.6 mmHg, P = 0.04) and endothelial function increased by 18.3% (from −3.5 ± 9.0% to 14.8 ± 8.1%, P < 0.001) in women . However, in men, endothelial function improved by 13% (from −1.3 ± 10.1% to 11.7 ± 6.2%, P < 0.001), but with no significant change in systolic blood pressure ( P = 0.29) or ankle–brachial index ( P = 0.8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations